SOCIAL MEDIA LITERACY FOR RURAL POPULATIONS AS AN INFORMATION SOURCE - Tayo, Yanti; Nursanti, Siti (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Sindangmukti Village, located in Karawang Regency, is home to a sizable population, although their only occupations are farming, labouring, and being female employees. As a result, Singaperbangsa University Karawang's community service program, Literacy about Digital Marketing, aims to improve residents' skills, particularly those of moms, kids, and teens. The ability of a person or organization to comprehend, make use of, and apply digital technology in marketing endeavours is known as digital marketing literacy. This includes being aware of social media, data analysis, and digital marketing strategies. To effectively sell their goods or services in the current digital world, individuals or companies need to be literate in digital marketing. Developing suitable digital marketing strategies, consulting, and training are a few instances of initiatives aimed at raising digital marketing literacy. Gaining proficiency in digital marketing in Indonesia can be very advantageous for people or businesses. Increasing the likelihood of business success through the use of organized digital marketing based on verified knowledge is one of the activities' pressing needs.